Kenosis and feminist theology the challenge of Gianni Vattimo - Frascati-Lochhead, Marta 1953- (McGill studies in the history of religions.)
This book addresses crucial issues that postmodern theory has raised for feminism and for feminist theology in particular. Postmodern critiques of metaphysics question whether feminism is ultimately foundationalist and essentialist, attributing an essential nature to "woman" and substituting a new metaphysical theory in place of the patriarchal foundationalism of Western thought. Marta Frascati-Lochhead develops this critique of metaphysics through a reading of the Italian philosopher, Gianni Vattimo.